2018
DOI: 10.1007/s13744-017-0571-6
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Recruitment and Foraging in the Ponerine Ant Pachycondyla harpax (Fabricius)

Abstract: Tandem running is a common recruitment strategy in ant species with small colony sizes. During a tandem run, an informed leader guides a usually naïve nestmate to a food source or a nest site. Some species perform tandem runs only during house hunting, suggesting that tandem running does not always improve foraging success in species known to use tandem running as a recruitment strategy, but more natural history information on tandem running under natural conditions is needed to better understand the adaptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 46 publications
2
31
0
Order By: Relevance
“…Ant species that are frequent users of EFN are known to nest closer to EFN-producing plants (Silva et al, 2019). Pachycondyla harpax usually nests underground in the vicinity of trees (Grüter et al, 2018), and although workers forage primarily on the ground, they can also be found on trees (Rocha et al, 2015). However, if P. harpax attends EFNs on I. edulis and P. gonoachanta trees needs to (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Ant species that are frequent users of EFN are known to nest closer to EFN-producing plants (Silva et al, 2019). Pachycondyla harpax usually nests underground in the vicinity of trees (Grüter et al, 2018), and although workers forage primarily on the ground, they can also be found on trees (Rocha et al, 2015). However, if P. harpax attends EFNs on I. edulis and P. gonoachanta trees needs to (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Even though some lost followers may discover the new nest by themselves (Pratt 2008; Franks et al 2010), unsuccessful tandem runs often represent a loss of time because lost followers require more time to discover a resource or they have to return to their nest following a break-up (Franks and Richardson 2006; Basari et al 2014b; Grüter et al 2018). Furthermore, a breakup could leave followers in unknown and dangerous locations.…”
Section: Discussionmentioning
confidence: 99%
“…A recruitment behaviour that relies on communication and that could be negatively affected by body size differences is tandem running, which is relatively common in ant species with small colony sizes (so far described in ~40 species) (Beckers et al 1989; Franklin 2014; Grüter et al 2018). During a tandem run, a leader with information about the location of a resource slowly guides a nestmate to a food source or a nest site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested that tandem running is the evolutionary precursor of odor-trail communication. In some species, the tandem running technique is only used during "house-hunting, " whereas other species explore tandem running in both migration and foraging (review in Grüter et al, 2018). This recruitment system has been considered to be a primitive one since only one nestmate is recruited at a time.…”
Section: Behavioral and Cognitive Individual Variability In Tandem Running Antsmentioning
confidence: 99%